A glycoconjugate-based gold nanoparticle approach for the targeted treatment of Pseudomonas aeruginosa biofilms - Zhang, Chao; Shi, De-Tai; Yan, Kai-Cheng; Sedgwick, Adam C.; Chen, Guo-Rong; He, Xiao-Peng; James, Tony D.; Ye, Bing; Hu, Xi-Le; Chen, Daijie (Nanoscale, 2020)
In this study, “core–shell” gold nanoparticles (AuNPs) have been functionalised using a simple one-pot approach to form fucose-based glycoconjugate AuNPs ( Fuc-AuNPs ) and galactose-based glycoconjugate AuNPs ( Gal-AuNPs ), respectively. Owing to the selective carbohydrate-based recognition of the key virulence factors of P. aeruginosa , LecB (fucose-specific lectin)/LecA (galactose-specific lectin), Fuc-AuNPs and Gal-AuNPs -based imaging and therapeutic strategies were evaluated towards P. aeruginosa . Both Fuc-AuNPs and Gal-AuNPs were non-covalently loaded with the fluorophore dicyanomethylene 4 H -pyran (DCM) to afford two highly selective fluorescence imaging agents for the visualisation of P. aeruginosa . The loading of Fuc-AuNPs and Gal-AuNPs with the known antibiotic Ceftazidime (CAZ) exhibited an enhanced therapeutic effect, illustrating the significance of this targeted drug delivery strategy. Exploiting the phototherapeutic properties of AuNPs, photoirradiation (600 nm) of Fuc-AuNP@CAZ/Gal-AuNP@CAZ provided both photothermal and photodynamic therapeutic (PTT/PDT) effects, which facilitated the release of CAZ. Fuc-AuNP@CAZ and Gal-AuNP@CAZ were shown to be effective photo/chemotherapeutics resulting in almost complete eradication of P. aeruginosa biofilms formed on clinically relevant surfaces (glass slides and steel surface).